Deferasirox chelation therapy in patients with transfusion‐dependent MDS: a 'real‐world' report from two regional Italian registries: Gruppo Romano Mielodisplasie and Registro Basilicata. (12th March 2015) - Maurillo, Luca; Breccia, Massimo; Buccisano, Francesco; Voso, Maria Teresa; Niscola, Pasquale; Trapè, Giulio; Tatarelli, Caterina; D'Addosio, Ada; Latagliata, Roberto; Fenu, Susanna; Piccioni, Anna Lina; Fragasso, Alberto; et al.
Abstract Deferasirox (DFX) is an orally administered iron chelator approved for use in patients with transfusion‐dependent iron overload due to myelodysplastic syndromes (MDS). The safety and efficacy of DFX has been explored in clinical trial settings, but there is little data on unselected patients with MDS. The aim of this study was to retrospectively evaluate the safety, compliance, efficacy and effect on haematopoiesis of DFX in a large 'real‐world' MDS population. One hundred and eighteen patients with transfusion‐dependent MDS were treated with DFX across 11 centres in Italy. Serum ferritin levels, haematological response, dosing, adverse events and transfusion dependence were recorded at baseline, 3, 6, 12 and 24 months following initiation of treatment. DFX reduced mean serum ferritin levels from 1790 to 1140 ng/mL (P < 0.001), with 7.1% of patients achieving transfusion independence. Significant haematological improvement was seen in erythroid (17.6%), platelet (5.9%) and neutrophil counts (7.1%). Adverse events were reported in 47.5% of patients, including gastrointestinal and renal toxicity. Regression analysis showed that higher starting doses of DFX are associated with transfusion independence at 24 months. DFX is a safe, effective treatment for transfusion‐dependent MDS that can lead to transfusion independence and haematological improvement in a subset of patients.